The Evolution of Seafloor Spreading Behind the Tip of the Westward Propagating Cocos‐Nazca Spreading Center. (15th June 2020) - Smith, Deborah K.; Schouten, Hans; Parnell‐Turner, Ross; Klein, Emily M.; Cann, Johnson; Dunham, Charles; Alodia, Gabriella; Blasco, Iker; Wernette, Benjamin; Zawadzki, Dominik; Latypova, Elvira; Afshar, Sara; et al.
Abstract: At the Galapagos triple junction in the equatorial Pacific Ocean, the Cocos‐Nazca spreading center does not meet the East Pacific Rise (EPR) but, instead, rifts into 0.4 Myr‐old lithosphere on the EPR flank. Westward propagation of Cocos‐Nazca spreading forms the V‐shaped Galapagos gore. Since ~1.4 Ma, opening at the active gore tip has been within the Cocos‐Galapagos microplate spreading regime. In this paper, bathymetry, magnetic, and gravity data collected over the first 400 km east of the gore tip are used to examine rifting of young lithosphere and transition to magmatic spreading segments. From inception, the axis shows structural segmentation consisting of rifted basins whose bounding faults eventually mark the gore edges. Rifting progresses to magmatic spreading over the first three segments (s1–s3), which open between Cocos‐Galapagos microplate at the presently slow rates of ~19–29 mm/year. Segments s4–s9 originated in the faster‐spreading (~48 mm/year) Cocos‐Nazca regime, and well‐defined magnetic anomalies and abyssal hill fabric close to the gore edges show the transition to full magmatic spreading was more rapid than at present time. Magnetic lineations show a 20% increase in the Cocos‐Nazca spreading rate after 1.1 Ma. The near‐axis Mantle Bouguer gravity anomaly decreases eastward and becomes more circular, suggesting mantle upwelling, increasing temperatures, and perhaps progression to a developed melt supply beneath segments. Westward propagation of individual Cocos‐Nazca segments is common with rates ranging between 12 and 54 mm/year. Segment lengths and lateral offsets between segments increase, in general, with distance from the tip of the gore. Plain Language Summary: A fundamental question in the study of mid‐ocean ridges is how spreading centers initiate and change through time. At the Galapagos triple junction in the equatorial Pacific, the oceanic crust is being broken apart to form rift basins, which develop into individual mid‐ocean ridge spreading segments. Bathymetry, magnetic, and gravity data were collected to help understand the stages in the transition from rift basins to a magmatic seafloor spreading center. From inception, the developing spreading center is composed of individual segments that are offset from each other. Currently, rifting progresses to magmatic spreading over three segments, which opened at slow spreading rates. Older spreading segments originated at faster‐spreading rates. Data indicate that the change from rifting to full magmatic spreading was more rapid in these older segments. Near the spreading axis, gravity data show that temperatures increase beneath segments as they mature, suggesting that magma supply is developing beneath the segments. Propagation of the western ends of segments is common. Understanding how seafloor spreading initiates and forms a segmented mid‐ocean ridge provides information on how mantle melting is established beneath a rift zone and how tectonic plate boundaries evolve. Key Points: At the Galapagos triple junction rifting changes to full magmatic spreading in stages within the Cocos‐Galapagos microplate spreading regime Magnetic anomalies and linear off‐axis topography show magmatic spreading developed rapidly when opening was between Cocos and Nazca plates Initial segment lengths at the tip of the Galapagos gore appear constant at ~20 km, but segment lengths are larger farther from the tip